Haasil - Shergill, Jimmy 1970-; Bhatt, Hrishitaa; Khan, Irrfan 1962-2020; Anand, Tinnu; Pandey, Sudhir; Saxena, Sharat; Zutshi, Rajendranath 1961-; Yadav, Rajpal 1973-; Ali, Murad; Sinhan, Aseem (Shemaroo Video, 2006)
Anirudh and Niharika, college students, fall in love but Anirudh is soon caught up in college politics dominated by two rivals. After Anirudh witnesses one of them commit murder, he is drawn deeper into political intrigue, gangs, and crime, threatening his relationship with Niharika
DVD; NTSC, all region; Dolby digital 5.1; digitally re-mastered from the original film. - Title in romanized and Hindi scripts. - Originally released as a motion picture in 2003. - Special feature: "making of" Haasil. - Includes song index
Keywords: College students / Political activity / India / Drama; Gangs / India / Drama; College students / Crimes against / India / Drama; Crime / India / Drama; Love / Drama; Musical films; College students / Crimes against; College students / Political activity; Crime; Gangs; Love; India; Indien; DVD-Video